Practical cognition as volition - Fix, J (Wiley, 2021)
Practical cognitivism is the view that practical reason is the self-conscious will and that practical cognition is self-conscious volition. This essay addresses two puzzles for practical cognitivism. In akratic action, I act as I understand is illegitimate and not as I understand is legitimate. In permissible action, I act as I understand is legitimate and also do not act as I understand is legitimate. In both types of action, practical cognition seems to come apart from volition. How, then, can practical reason be our will and practical cognition be volition? Practical cognitivists can solve these puzzles because the claims that practical reason is our will and that practical cognition is volition are about the nature of a capacity, and the nature of a capacity establishes standards of correctness for its exercises. Akratic action is a type of erroneous exercise of practical reason as tripping is an erroneous exercise our capacity to walk. Permissible action is a successful exercise of practical reason as stepping first with my right foot rather than my left is a successful exercise of my capacity to walk. The puzzles of akratic and permissible action do not refute practical cognitivism.